TINJAUAN YURIDIS TERHADAP PERBUATAN INGKAR JANJI DI ATAMBUA DITINJAU DARI PUTUSAN PENGADILAN NEGERI ATAMBUA NOMOR 39/Pdt.G/2020/PN Atb - Ngahu, Yunita Kana (Kerta Dyatmika, 2018)
The act of breaking a promise in marriage as an unlawful act known as a marriage case is a legal agreement entered into by one of the parties which causes incompatibility within the two families, those are the act of breaking a promise to marry. This phenomenon often occurs when the party promising to marry breaks the agreement or does not keep the promises made, and many cases like this often occur but are not followed up through the legal process. The formulation of the problem is how the legal regulations and customary sanctions are given to one party who does not fulfill or breaks the agreement in marriage. This type of research uses normative legal research, which moves from the absence of norms to a situation where there is an absence of legal norms in regulation of a matter so that this research approach uses a statutory regulations approach, a legal concept approach, a historical approach. The results of the research show that the legal regulation of the act of breaking a promise to marry is contained in Article 1365 of the Civil Code, where the victim of breaking a promise act be able to obtain restoration of the promised rights and compensation for the loss. Juridical Review of Atambua District Court Decision No. 39/Pdt.G/2020/PN Atb. The judge in this case stated that he punished the plaintiff for carrying out his legal obligations towards the plaintiff and ordered the defendants jointly and severally to pay the Wc Wehali customary sanctions. Customary sanctions are still applied in accordance with customary law because both parties have gotten to know each other through the Tanasak exchange and the customary fines are adjusted to the current situation. .